(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2022)
Online garnishment is a fast-foward effectiveness tool on tax enforcement. The new law of Abuse of authority criminalized the non-release of excess of blocked amounts. The new penal act is ought to be unconstitutional.